Determining Long-Term Probabilities for Labor Absorption from the Realization of Domestic Investment (PMDN) and Foreign Investment (PMA) in Indonesia Using Markov Chain Analysis: Determining Long-Term Probabilities for Labor Absorption from the Realization of Domestic Investment (PMDN) and Foreign Investment (PMA) in Indonesia Using Markov Chain Analysis - binti Syed Jaaffar, Sharifah Arni; Ibrahim, Riza Andrian (International Journal of Mathematics, Statistics, and Computing, 2023)
The government through President Joko Widodo in a press conference stated that the Job Creation Law is very urgent to be passed immediately, even though it has received a lot of resistance in society. The government stated that the bureaucracy in investing in Indonesia is still convoluted, so the possibility of a decrease in employment in the future is very high. However, this was denied by Faisal Basri. This reason is not in accordance with the current state of investment, he concluded. Realization of Domestic Investment (PMDN) and Foreign Investment (PMA) in Indonesia tends to always increase every year, so it is not the investment bureaucracy that is the cause of decreased employment. Abdul Malik said that, the reason for the decrease in absorption labor is the lack of competitiveness of the local workforce and the government's lack of selectiveness in choosing investments that enter Indonesia. This study aims to provide consideration for the government, in the form of long-term employment probabilities from the realization of PMDN and PMA in Indonesia which are calculated using Markov chain analysis. The calculation results obtained are that the long-term probability of increasing the amount of labor absorption from the realization of PMDN and PMA is 0.56 or 56%, while the long-term probability of decreasing is 0.44 or 44%. Then, in specific intervals, the possibility of an increase in the workforce of at most 93 thousand people is very high, namely 0.42 or 42%. This value is greater than the possibility of a decrease in the workforce of at most 93 thousand people, namely 0.27 or 27%. This value is contrary to the government's assumption which states that the possibility of a decrease in labor absorption is very high. Therefore, the results of this research can be used as one of the considerations for the government to rethink the urgency of issuing the Job Creation Law.